Interleukin-6 trans-signaling is a candidate mechanism to drive progression of human DCCs during clinical latency - Melanie Werner-Klein (Nature Portfolio, 2020)
Metastatic dissemination in breast cancer patients occurs early in malignant transformation, raising questions about how disseminated cancer cells (DCC) progress at distant sites. Here, the authors show that DCCs in bone marrow are activated via IL6-trans-signaling and thereby acquire stemness traits relevant for metastasis formation.